Biophysical and structural studies of aggregation of nucleosome core particle with charge modified histone proteins. - Liu, Ying. (2012)
The core histone proteins H2A, H2B, H3 and H4 constitute the spool for the DNA hierarchical packaging in eukaryotes and form the basic chromatin structural unit of the nucleosome core particle (NCP). The positive charges on the histone H4 N-terminal tails extensively interact with DNA through electrostatic interactions, and with the H2A-H2B dimer of adjacent NCPs through structural specific interactions. Therefore, reduction of the H4 tail positive and the H2A core negative charges through acetylation or mutations would interrupt DNA-histone or inter-nucleosome associations. Such processes resemble the opening up of chromatin fiber structure that consequently leads to increased DNA accessibility and active gene transcription.